A systematic review of the staging performance of endoscopic ultrasound in gastro-oesophageal carcinoma. (1st October 2001) - Kelly, S; Harris, K M; Berry, E; Hutton, J; Roderick, P; Cullingworth, J; Gathercole, L; Smith, M A
Abstract : BACKGROUND: Endoscopic ultrasound (EUS) may be used for preoperative staging of gastro-oesophageal carcinoma but performance values given in the literature differ. AIMS: To identify and synthesise findings from all articles on the performance of EUS in tumour, node, metastasis (TNM) staging of gastro-oesophageal carcinoma. SOURCE: Published and unpublished English language literature, 1981–1996. METHODS: Data on the staging performance of EUS were retrieved and evaluated. Summary receiver operator characteristic methodology was used for synthesis, and a summary estimate of performance, Q*, obtained. Multiple regression analysis was used to assess study validity and investigate reasons for differences in performance. RESULTS: Twenty seven primary articles were assessed in detail. Thirteen supplied results for staging oesophageal cancer, 13 for gastric cancer, and four for cancers at the gastro-oesophageal junction. For gastric T staging, Q*=0.93 (95% confidence interval (CI) 0.91–0.95) and for oesophageal T staging, Q*=0.89 (95% CI 0.88–0.92). For gastro-oesophageal T staging, including cancers at the gastro-oesophageal junction, Q*=0.91 (95% CI 0.89–0.93). Inclusion of cases with non-traversable stenosis was found to slightly reduce staging performance. For N staging, Q*=0.79 (95% CI 0.75–0.83). In articles that compared EUS directly with incremental computed tomography, EUS performed better. None of the variables assessed in the regression analysis was significant using a Bonferroni correction. Three variables (anatomical location, traversability, and blinding) showed strong relationships for future research and validation. CONCLUSIONS: EUS is highly effective for discrimination of stages T1 and T2 from stages T3 and T4 for primary gastro-oesophageal carcinomas. The failure rate of EUS from non-traversability of a stenotic cancer may be a limitation in some patient groups.